Analisis Sistem Pentanahan Gardu Induk 150 KV Maninjau Dengan Kontruksi (Grid- Rod) - Mhd. Fadly; Suwitno Suwitno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The substation is are an important part of the electric power system to distribute electric power to other substations. Substations have the potential to experience disturbances, one of which is lightning strikes and overcurrents. To avoid the possibility of dangerous interference, the substation must have a grounding system that meets safe standards for equipment and people around the substation’s area. The grounding system is a part of the electric power system which has the function of grounding in the event of a disturbance. In this study, the construction method (grid-rod) was used to analyze the grounding system at the 150 kV Maninjau substation. From the calculation results, the total fault current is 1732 A, the grounding grid resistance is 0.115 Ω, the mesh voltage value is 42,96 V, the permissible touch voltage is 991.1 V, the step voltage is 103.92 V and the permissible step voltage is 3298.2 V. The total length of conductors for the earthing grid used is 3390,5 m with 11 conductors parallel to the X axis and 23 parallel to the Y axis. Keyword : substation, fault, grounding, grid-rod